Giant Electro‐Optical Effect through Electrostriction in a Nanomechanical Metamaterial. Issue 1 (6th November 2018) - Karvounis, Artemios; Gholipour, Behrad; MacDonald, Kevin F.; Zheludev, Nikolay I.
Abstract: Electrostriction is a property of all naturally occurring dielectrics whereby they are mechanically deformed under the application of an electric field. It is demonstrated here that an artificial metamaterial nanostructure comprising arrays of dielectric nanowires, made of silicon and indium tin oxide, is reversibly structurally deformed under the application of an electric field, and that this reconfiguration is accompanied by substantial changes in optical transmission and reflection, thus providing a strong electro‐optic effect. Such metamaterials can be used as the functional elements of electro‐optic modulators in the visible to near‐infrared part of the spectrum. A modulator operating at 1550 nm with effective electrostriction and electro‐optic coefficients of order 10 −13 m 2 V −2 and 10 −6 m V −1, respectively, is demonstrated. Transmission changes of up to 3.5% are obtained with a 500 mV control signal at a modulation frequency of ≈6.5 MHz. With a resonant optical response that can be spectrally tuned by design, modulators based on the artificial electrostrictive effect may be used for laser Q ‐switching and mode‐locking among other applications that require modulation at megahertz frequencies. Abstract : A nanomechanical metamaterial providing electro‐optic modulation via electrostriction is demonstrated. The modulator, which comprises arrays of bilayer silicon/indium tin oxide nanowires that are reversibly deformed under the application of an electric field, operates at 1550 nm with effective electrostriction and electro‐optic coefficient orders of magnitude larger than those of bulk dielectrics (reaching 10 −13 m 2 V −2 and 10 −6 m V −1, respectively).